PRAKTEK POLITIK UANG DALAM PEMILU LEGISLATIF 2014 (Studi Kasus di Kabupaten Blora) - DENDY LUKMAJATI (Politika: Jurnal Ilmu Politik, 2016)
Abstrac What so-called “money politics” practices occurred during the legislative election is well-known publicly, including happened in Blora District. Even this practices are caught by election supervision committee based on the information from local people in Tambahrejo Village, Tunjungan Subdistrict. In many cases, however, this money politics practices rarely uncovered due to its secrecy nature including the cases which reported officially to the committee such as in Randublatung Subdistrict. Those money politics practices never been resolved and only became an allegations. This research more focused on the public perceptions about the practices of money politics during the legislative elections, including how the public response on this issue and the degree of their objectivity to vote the candidates.Keywords:  Legislative election, money politics, perception